The Opposition to Caesar Worship - Scott, Ernest Findlay (Church history, 1933)
It was on the question of Caesar worship that Christianity and Paganism joined battle. They were radically opposed, but the conflict broke out on this definite issue; and its real nature has commonly been misunderstood.There is no occasion, in this brief paper, to discuss the origin and history of the imperial cult. Enough to say that its motive was at once political and religious. On the one hand it was nothing but a civic ritual, by means of which the diverse races could express their common loyalty to the empire. It did not seek to displace any existing religion. It was not so much a mode of worship as a patriotic gesture, like the salutation of the flag. Yet it did, in some measure, answer to a religious need. The old religions were all associated with the tribes or cities which practised them, and had lost their purpose when these were absorbed in the composite empire. What was to be the religion of the empire itself, which was now being organised as a single corporate state? To the ancient mind a political system was unthinkable apart from a religious sanction, and since there was no traditional cult on which all the races could unite, a new one had to be devised. It found its object of worship in the state itself, as represented by its supreme ruler.